2019
DOI: 10.1111/ejss.12867
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microwave disinfestation treatments on the bacterial communities of no‐till agricultural soils

Abstract: Growing herbicide resistance has encouraged the development of new technologies for weed control. Microwave (MW) heating of soil before sowing has been shown to reduce weed establishment in no-till farming systems and substantially increases crop productivity. However, the effect of this technology on the soil microbial community in general, and on beneficial soil microbes such as ammonia oxidizers in particular, warrants further study. In order to check the effect of MW soil disinfestation treatments on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…The temperature distribution is proportional to the square of the microwave field distribution and is determined from this squared field distribution by integration with √ , as outlined by Crank [20]: www.videleaf.com (4) The resulting temperature distribution is described by a Voigt…”
Section: Theoretical Analyses Of a Slow-wave Structure Used For Heatingmentioning
confidence: 99%
“…The temperature distribution is proportional to the square of the microwave field distribution and is determined from this squared field distribution by integration with √ , as outlined by Crank [20]: www.videleaf.com (4) The resulting temperature distribution is described by a Voigt…”
Section: Theoretical Analyses Of a Slow-wave Structure Used For Heatingmentioning
confidence: 99%
“…Br. ), parthenium (Parthenium hysterophorus L.) and bellyache bush (Jatropha gossypiifolia L.) [36] Effects of microwave treatment on growth, photosynthetic pigments and some metabolites of wheat [66] Microwave seed treatment reduces hardseededness in Stylosanthes seabrana and promotes redistribution of cellular water as studied by NMR relaxation measurements [67] Effect of microwave fields on the germination period and shoot growth rate of some seeds [68] Germination of Chenopodium album in Response to Microwave Plasma Treatment [69] Work conditions for microwave applicators designed to eliminate undesired vegetation in a field [70] microwave treatment (Figure 7), Khan et al [72] demonstrated that immediately after microwave soil treatments, the relative abundance of Firmicutes increased while the relative abundance of Proteobacteria decreased significantly. They also showed that the relative abundances of beneficial soil microbes (Micromonosporaceae, Kaistobacter and Bacillus) were significantly higher, as soils recovered from high heating intensities induced by microwave soil treatment, compared with untreated soils.…”
Section: Paper Title Referencementioning
confidence: 99%
“…This may be due to the resilience of nitrifying bacteria and archaea to microwave soil heating. Khan et al [72] showed that microwave soil treatment did not significantly affect ammonia oxidizing bacteria or ammonia oxidizing archaea. Vela et al [74] also demonstrated that nitrifying bacteria in the soil were resilient to 40 kJ cm À2 of microwave energy at the soil surface; which is 70 times higher than the energy densities used during experimental work undertaken by the current authors.…”
Section: Paper Title Referencementioning
confidence: 99%
“…A key conclusion is that soil management practices need improvement in many NT systems to increase earthworm populations. A soil biological focus was also investigated by Khan, Jurburg, He, Brodie, & Gupta (2020), who studied the effect of microwave heating (a means to control weeds) on bacterial communities in an Australian NT soil, a Red Mesotrophic‐Haplic Dermosol (Australian soil classification). High‐temperature treatments caused irreversible damage to bacterial community richness and only heat‐resistant bacterial taxa could survive.…”
Section: Specific Nt Impacts On Physical Chemical and Biological Promentioning
confidence: 99%